Quantification and correlation of amyloid-β plaque load, glial activation, GABAergic interneuron numbers, and cognitive decline in the young TgF344-AD rat model of Alzheimer’s disease - Futácsi, Anett; Rusznák, Kitti; Szarka, Gergely; Völgyi, Béla; Wiborg, Ove; Czéh, Boldizsár (Frontiers in Aging Neuroscience, 2025)
BackgroundAnimal models of Alzheimer’s disease (AD) are essential tools for investigating disease pathophysiology and conducting preclinical drug testing. In this study, we examined neuronal and glial alterations in the hippocampus and medial prefrontal cortex (mPFC) of young TgF344-AD rats and correlated these changes with cognitive decline and amyloid-β plaque load.MethodsWe compared TgF344-AD and non-transgenic littermate rats aged 7–8 months of age. We systematically quantified β-amyloid plaques, astrocytes, microglia, four different subtypes of GABAergic interneurons (calretinin-, cholecystokinin-, parvalbumin-, and somatostatin-positive neurons), and newly generated neurons in the hippocampus. Spatial learning and memory were assessed using the Barnes maze test.ResultsYoung TgF344-AD rats had a large number of amyloid plaques in both the hippocampus and mPFC, together with a pronounced increase in microglial cell numbers. Astrocytic activation was significant in the mPFC. Cholecystokinin-positive cell numbers were decreased in the hippocampus of transgenic rats, but calretinin-, parvalbumin-, and somatostatin-positive cell numbers were not altered. Adult neurogenesis was not affected by genotype. TgF344-AD rats had spatial learning and memory impairments, but this cognitive deficit did not correlate with amyloid plaque number or cellular changes in the brain. In the hippocampus, amyloid plaque numbers were negatively correlated with cholecystokinin-positive neuron and microglial cell numbers. In the mPFC, amyloid plaque number was negatively correlated with the number of astrocytes.ConclusionPronounced neuropathological changes were found in the hippocampus and mPFC of young TgF344-AD rats, including the loss of hippocampal cholecystokinin-positive interneurons. Some of these neuropathological changes were negatively correlated with amyloid-β plaque load, but not with cognitive impairment.